2015
DOI: 10.1103/physrevlett.114.243001
|View full text |Cite
|
Sign up to set email alerts
|

High-AccuracyCO2Line Intensities Determined from Theory and Experiment

Abstract: Atmospheric CO 2 concentrations are being closely monitored by remote sensing experiments which rely on knowing line intensities with an uncertainty of 0.5% or better. Most available laboratory measurements have uncertainties much larger than this. We report a joint experimental and theoretical study providing rotation-vibration line intensities with the required accuracy. The ab initio calculations are extendible to all atmospherically important bands of CO 2 and to its isotologues. As such, they will form th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
108
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 114 publications
(117 citation statements)
references
References 44 publications
(56 reference statements)
7
108
0
Order By: Relevance
“…For this DMS, dipole moment components μ A were calculated using the finite field procedure with an external field value of ±5 × 10 −5 a.u. For both water [49] and carbon dioxide [50] we have demonstrated that even though the finite field method requires seven times more computations than using expectation values, the resulting DMS is more accurate. Calculations were performed using internally contracted MRCI in the full valence reference space comprising 8 electrons in 7 orbitals, with the aug-cc-pwCVQZ basis set.…”
Section: Intensity Simulationsmentioning
confidence: 95%
“…For this DMS, dipole moment components μ A were calculated using the finite field procedure with an external field value of ±5 × 10 −5 a.u. For both water [49] and carbon dioxide [50] we have demonstrated that even though the finite field method requires seven times more computations than using expectation values, the resulting DMS is more accurate. Calculations were performed using internally contracted MRCI in the full valence reference space comprising 8 electrons in 7 orbitals, with the aug-cc-pwCVQZ basis set.…”
Section: Intensity Simulationsmentioning
confidence: 95%
“…This is done, at least in part, to aid the predictions of the rotational spectrum of these species and hence their detection in the laboratory and space [181,182]. One area where uncertainty assessment is beginning to have significant impact is the computation of dipole-moment surfaces [59,60] and hence rotation-vibration transition intensities [184]. The methodology used here is based on adapting the FPA method for computing the dipole moment surface (DMS) and then performing multiple computations using different PESs and DMSs to establish stability of the results [185,186].…”
Section: Illustrationsmentioning
confidence: 99%
“…The values used by the OCO-2 algorithm are based on Devi et al (2007Devi et al ( , 2016. Values from Polyansky et al (2015) differ from those in Devi et al (2016) by ∼ 1.2 %.…”
Section: Forward Model Errormentioning
confidence: 99%